Faktor-faktor yang Mempengaruhi Perataan Laba - Verinaapril Milaedy; Cahyani Nuswandari; Muhammad Ali Ma'sum (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Earnings information is often the target of management engineering to maximize its satisfaction because there are parties who pay attention to profits so that it encourages management to take action in managing earnings or earnings management. One of the earnings management actions that are often carried out by several companies to beautify their financial statements is income smoothing. This study aims to analyze the effect of return on assets, debt to equity ratio, bonus plan and income tax on income smoothing. The analytical method used in this research is logistic regression analysis. The results of this study indicate that return on assets has a positive and significant effect on income smoothing, the debt to equity ratio and bonus plan have a negative and significant effect on income smoothing, while income tax has no significant effect on income smoothing. Keywords: income smoothing; return on assets; debt to equity ratio; bonus plan; income tax